Knowledge, attitude and predictors of diabetic retinopathy screening among patients with type 2 diabetes in Nairobi County, Kenya - Lagatt C Faith; Harun Kimani (Journal of Health and Social Sciences)
Introduction: Aim of this study was to explore the level of knowledge and attitude towards diabetic retinopathy screening as well as predictors of its utilization amongst People Living With Diabetes (PLWD) in Nairobi County, Kenya. Methods: A mixed-method cross-sectional study design was employed. Multistage sampling technique was adopted for selecting persons with diabetes attending ‘level three’ health facilities. A questionnaire ad hoc was developed and used. Ordinal logistic regression models with stepwise method were employed on variables with statistical significance at chi square tests (P < 0.05) to determine the significant predictors of diabetic retinopathy screening. Results: A total of 200 patients (rate of respondents: 96%) participated in the study. Our findings revealed a low utilization level (n = 21, 10.5%) of diabetic retinopathy screening by participants. Significant predictors of utilization of diabetic retinopathy screening were education level [(OR = 4.411; 95% Confidential Interval (CI) 1.504 to 28.636; P = 0.018)], presence of family history of diabetes (OR = 11.112; CI 1.554 to 59.444; P = 0.016), and primary clinician referral (OR = 3.263, CI 1.498 to 21.357; P = 0.027). Discussion and Conclusion: There is poor knowledge by PLWD in Kenya on the recommended frequency of diabetic retinopathy screening. Moreover, PLWD showed poor attitude towards DR screening utilization, which could be attributed to insufficient knowledge on the importance of regular retinal examination. Educational messages developed by government and policymakers should focus on the recommended interval for eye examinations, importance of regular diabetic retinopathy screening and empowering PLWD to request/demand for eye examination. Target population should include PLWD, their families, health care providers and the general public.